2020
DOI: 10.3390/nu12041100
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Protects against Memory and Hippocampal Neurogenesis Depletion in D-Galactose-Induced Aging in Rats

Abstract: The interruption of hippocampal neurogenesis due to aging impairs memory. The accumulation of D-galactose (D-gal), a monosaccharide, induces brain aging by causing oxidative stress and inflammation, resulting in neuronal cell damage and memory loss. Chrysin, an extracted flavonoid, has neuroprotective effects on memory. The present study aimed to investigate the effect of chrysin on memory and hippocampal neurogenesis in brains aged using D-gal. Male Sprague-Dawley rats received either D-gal (50 mg/kg) by i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…36 Therefore, the brain is more sensitive to D-gal, and accumulation of D-gal can induce brain damage and lead to neuronal cell damage and memory loss, particularly in the hippocampal pyramidal cells. 7,37 In the present work, D-gal evidently caused shrinkage, disarrangement, and even vacuolation of pyramidal neurons in the CA1 area of the hippocampus, while CSE significantly improved the pathological damage of the hippocampus (Fig. 1).…”
Section: Food and Function Papersupporting
confidence: 57%
See 1 more Smart Citation
“…36 Therefore, the brain is more sensitive to D-gal, and accumulation of D-gal can induce brain damage and lead to neuronal cell damage and memory loss, particularly in the hippocampal pyramidal cells. 7,37 In the present work, D-gal evidently caused shrinkage, disarrangement, and even vacuolation of pyramidal neurons in the CA1 area of the hippocampus, while CSE significantly improved the pathological damage of the hippocampus (Fig. 1).…”
Section: Food and Function Papersupporting
confidence: 57%
“…However, a D-gal overload can cause the accumulation of galactitol and excessive reactive oxygen species (ROS) production, resulting in oxidative stress, formation of advanced glycation end-products, neuronal cell death, cognitive decline, and reduction of antioxidant enzymes, and ultimately lead to tissue damage. [6][7][8] Considerable evidence has shown that inhibiting oxidative stress can prevent or treat aging-related diseases. 1,9 The brain is particularly vulnerable to oxidative stress compared with other organs because of its high oxygen metabolism rate and relative lack of free radical scavenging enzymes and antioxidant molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nine sections were used for staining using a free floating method. p21-positive cells within three cells of the inner edge in the upper and lower blade of the DG were counted [ 10 , 11 , 37 ]. Sections were viewed at 10 × and 40 × by a Nikon ECLIPSE 80i fluorescence microscope (Melville, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The accumulation of D-galactose induces brain aging due to oxidative stress and inflammation, leading to neuronal cell damage and memory loss. The administration of chrysin at the doses of 10 or 30 mg kg −1 in rats with D-galactose-induced memory disorders reversed neuronal pathological changes and attenuated the memory impairments associated with aging [84].…”
Section: Chrysin In Neurodegenerative and Eye Diseasesmentioning
confidence: 94%
“…Chrysin also has such an activity and improves the processes involved in memory [83]. It regulates neurogenesis in memory loss due to aging [84]. It has also neuroprotective effect on SH-SY5Y neuronal cells treated with diclofenac [68].…”
Section: Chrysin In Neurodegenerative and Eye Diseasesmentioning
confidence: 99%